Fraksinasi dan Identifikasi Senyawa Volatil Asap Cair Cangkang Sawit - Muhammad Halim; Purnama Darmadji; Retno Indrati (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2005)
Palm kernel shell is one residue material of oil palm process industry. Total palm kernel shell were sufficient and could be processed into liquid smoke. The liquid smoke has been found to contain compounds functioning as smoky product improvement. This research was to identify volatile compound components existing in the liquid smoke of pabn kernel shell. This research started from liquid smoke production by pirolisa at 400 °C for 90 minutes and fractionation of temperature variation <100°C(F1), 101-125°C(F2), 126-150°C(F3), 151-175°C(F4), and 176-200°C(F5). The results of fractionation were analysed for the following chemical compositions: phenol, carbonyl, acid, and pH. The volatile compound components of liquid smoke was identified using GC-MS. The result of research indicated that F2 had highest content was 82.26%. The content of phenol, carbonyl, and acid of liquid smoke were 3.86%, 12.48%, and 12.41% respectively. The results of fractionation of phenol content low in F1 increased to F5 of 0.73%. The content of carbonyl was lower and the lowest in F5 was 3.61%. The content of acid was higher and the highest in F5 was 63.81% along with pH of liquid smoke (F0) of 3.29 and more acidy in F5 of 2.69. The result of GC-MS indicated that the liquid smoke consisted of at least 14 high components. Some of them were phenol, 2-methoxy 4-methyl phenol, 2-furan carboxaldehyde, 1,2-benzenediol, 2-methyl phenol, 4-ethyl 2-methoxy phenol, 1,2,3-trimethoxy phenol, 3-methoxy 1,2-benzenediol, 3-methyl 1,2-cyclopentanedione, 1,2,3-trimethoxy 5-methyl benzene, dan 2,3-penthanedione